The Penerapan Metode Customer Satisfaction Index Kepuasan Konsumen Terhadap Pelayanan Toko Cikal Aquarium - Pasaribu, Satria; Sovina, Mutiara (Computer Science and Information Technology, 2025)
This study aims to determine the level of customer satisfaction with the services at Toko Cikal Aquarium by applying theCustomer Satisfaction Index (CSI) method. The store faces several issues, including a manual sales system, difficulties inobtaining customer satisfaction data, and the lack of a digital platform to support service quality evaluation. This researchadopts a quantitative approach with data collection methods including observation, interviews, and questionnaires. The CSImethod is used to analyze key service attributes such as location, individual service, store attributes, and product quality. Thesystem design follows the waterfall approach, utilizing PHP for programming, MySQL for the database, and UML modelingtechniques such as use case, class, activity, and sequence diagrams. The results show that implementing the CSI method in aweb-based system enables the seller to more easily identify which attributes influence customer satisfaction and makeimprovements based on the collected data. This system also facilitates documentation, evaluation, and strategic decision-makingin managing services at Toko Cikal Aquarium.